METHODOLOGICAL ASPECTS OF IMPROVEMENT OF QUALITY CONTROL OF HYDRAULIC LIQUIDS IN THE CONTEXT OF THE MECHANISM OF AIRCRAFT SAFETY CONTINUOUS MONITORING - Кузнєцова, О.; Нетреба, Ж.; Бойченко, М.; Кліщ I. (Science-based technologies, 2012)
In the article the shown possibility of prognostication of level of operating properties of hydraulic liquids is during their protracted use, that is base on the direction of the chemical converting set experimentally into their hydrocarbon composition. The indexes of quality, that can be select the pointers of level of quality of hydraulic liquid at the protracted use that does possible to appoint periodicity of control of quality of hydraulic liquids and create the mechanism of the continuous monitoring of safety of the hydraulic system of air ship, are found.